Konsep Dasar Literasi Dalam Upaniṣad Sebagai Upaya Peningkatan Mutu Pendidikan - Ni Kadek Surpi; I Komang Dian Adi Purwadi (Jurnal Penjaminan Mutu, 2021)
Literacy is the soul of education In Hindu civilization. The Upanisad is an integral part of Vedic literature. It provides the basic concepts of education and literacy patterns. According to the Upanisad, education is about giving educated degrees to students and building excellent human character. Likewise, literacy is essential in Hindu Education. This article will explain the basic concepts of education and literacy patterns in the Upanisad, which are the basis for human resource development, as stated in ancient texts. This study uses Vedic hermeneutics to explain and construct the superiority of the concepts contained in the Upanishads.